Aquaculture and the Environment in the United States - Craig S. Tucker; John A. Hargreaves; Claude E. Boyd (John Wiley & Sons Ltd., 2025)
. . . the animals which live in the watery depths, above all in ocean waters . . . are protected against the destruction of their species at the hand of man. Their reproductive rate is so large and the means which they have to save themselves from his pursuits or traps are such that there is no evidence that he can destroy the entire species of any of these animals.